Iphone for dummies, 13th edition - Baig, Edward C. (For Dummies, 2020)
Unleash the power of your iPhone! The iPhone you carry in your pocket or purse gives you enormous power to get things done. It puts you within easy reach of your family and friends, provides instant access to your favorite music, TV, and movies, lets you to follow and react to news and events, and makes it possible to share your life in pictures and video with anyone in the world-all within seconds. And this is just scratching the surface of what it can do! This updated edition of iPhone for Dummies covers the latest versions of the device and the latest version of the iOS operating system. Beginning with how to get started with a new phone-navigating the settings, hooking up to wifi, sharing audio and video - you'll also find out the many ways in which the iPhone's tools and applications can bring an extra dimension to all aspects of your life. Explore the latest version of iOS Change your life with must-have apps Get artsy with photos, videos, and creative applications Troubleshoot common problems with ease Whether you're just getting started or want to get even more from your iPhone, this book puts all the power in your hands!